2016
DOI: 10.1111/imj.12919
|View full text |Cite
|
Sign up to set email alerts
|

Improving discharge planning communication between hospitals and patients

Abstract: A bedside 'Leaving Hospital Information Sheet' can potentially improve communication between patients, families and their treating team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Discharge summaries and discharge letters often miss substantial and essential patient information [ 32 ] few data is passed over for the healthcare continuum. Previous studies found that proposed discharge date and destination collection from patients with interdisciplinary collaboration teams, raised the perceptions of patients’ awareness of discharge plans, prevented unnecessary delays in discharge, and provided physicians about alternative destinations regarding older patients’ preferences [ 33 ]. Another aspect to consider in Korea, is to utilize nursing communication.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge summaries and discharge letters often miss substantial and essential patient information [ 32 ] few data is passed over for the healthcare continuum. Previous studies found that proposed discharge date and destination collection from patients with interdisciplinary collaboration teams, raised the perceptions of patients’ awareness of discharge plans, prevented unnecessary delays in discharge, and provided physicians about alternative destinations regarding older patients’ preferences [ 33 ]. Another aspect to consider in Korea, is to utilize nursing communication.…”
Section: Discussionmentioning
confidence: 99%
“…Across the ED literature, effective communication continues to be a challenge for all age groups (New et al, 2016; Newnham et al, 2017) and can be compounded in the presence of functional disability or cognitive impairment (Miller et al, 2018). Yet, communication is fundamental to ensure family and patient satisfaction, safety, and person‐centred care (Considine et al, 2019; New et al, 2016; Newnham et al, 2017). This study has highlighted that family social support can assist with communication and information sharing in the ED and for discharge preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Wait times were shorter in the screening group than in the usual group for all 4 categories of discharge destinations. Improving hospital patient ow is important to optimize the use of limited healthcare resources e ciently and minimize iatrogenic adverse events, and it may ensure patient-centered care [18]. A screening tool for DP would make the transition of care from the hospital to the next destination more effective.…”
Section: Discussionmentioning
confidence: 99%